When You Read This : a Novel - Adkins, Mary (New York, NY : [Harper], an imprint of HarperCollinsPublishers, 2019)
"After PR power Iris Massey dies from a terminal illness at age 33, friend and colleague Smith learns that in her final months she created a blog full of acute observations on a life cut short. He wants to publish it, but that will require the cooperation of Iris's despairing chef sister, Jade"--Publisher's description.
Keywords: Publishers and publishing -- Fiction; Friendship -- Fiction; Interpersonal relations -- Fiction; Epistolary fiction